2015
DOI: 10.1093/ndt/gfv014
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent FXYD2 p.Gly41Arg mutation in patients with isolated dominant hypomagnesaemia

Abstract: The recurrent p.Gly41Arg FXYD2 mutation in two new families with IDH confirms that FXYD2 mutation causes hypomagnesaemia. Until now, no other FXYD2 mutations have been reported which could indicate that other FXYD2 mutations will not cause hypomagnesaemia or are embryonically lethal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 21 publications
(28 reference statements)
0
39
0
Order By: Relevance
“…4, 20 Indeed, heterozygous mutations in FXYD2 are known to cause autosomal dominant hypomagnesemia with hypocalciuria (OMIM: 154020). 21, 22 Whether the regulation of FXYD2 by HNF1β is sufficient to explain the symptoms in ADTKD-HNF1β is being questioned. 23 Current studies on HNF1β binding sites depend mainly on bioinformatical identification of the HNF1β recognition sequence in gene promoters.…”
Section: Introductionmentioning
confidence: 99%
“…4, 20 Indeed, heterozygous mutations in FXYD2 are known to cause autosomal dominant hypomagnesemia with hypocalciuria (OMIM: 154020). 21, 22 Whether the regulation of FXYD2 by HNF1β is sufficient to explain the symptoms in ADTKD-HNF1β is being questioned. 23 Current studies on HNF1β binding sites depend mainly on bioinformatical identification of the HNF1β recognition sequence in gene promoters.…”
Section: Introductionmentioning
confidence: 99%
“…In the distal convoluted tubule, Mg 2+ reabsorption is achieved via transient receptor potential melastatin type 6 (TRPM6) Mg 2+ channels and is dependent upon the voltage gradient set by the Na + -K + -ATPase. Indeed, patients with mutations in FXYD2 , which encodes the γ-subunit of the Na + -K + -ATPase, suffer from hypomagnesemia and renal Mg 2+ wasting [6] . In addition, it has been shown that HNF1B, together with its dimerization factor PCBD1, regulates the transcription of FXYD2 , which explains why HNF1B and PCBD1 mutations result in renal Mg 2+ wasting [3,7] .…”
Section: Introductionmentioning
confidence: 99%
“…The phenotype produced is reminiscent of the rare genetic disorder, isolated dominant hypomagnesemia, which is associated with urinary Mg wasting [9]. In this condition, linkage analysis identified the genetic defect as a G41R mutation in the FXYD2 gene, which encodes the γ subunit of the Na,K-ATPase [6, 10, 11]. This is clearly a loss of function mutation, which causes a dominant negative effect, and misrouting of the γ subunit to the plasma membrane [6].…”
Section: Discussionmentioning
confidence: 99%